Coverage of Forced Migration in Nigeria: A Content Analysis of Three National newspapers: Coverage of Forced Migration in Nigerian Dailies - OKPOKO, CHINWE; OKORONKWO, MOSES; UCHE OKPOKO, PAT; Catherine Okpoko, Chinwe (International Journal of Psychosocial Rehabilitation, 2024)
Forced migration has become a subject of serious concern in global discourses including Nigeria. An estimated over two million people have sought safe havens in Internally Displaced Persons (IDPs) camps located in parts of Nigeria, following the increased social dislocation engendered by Boko-Haram insurgency, Fulani herdsmen attacks, communal and ethnoreligious clashes, disputes over land, boundary conflicts between indigenous people and settlers, natural disasters and environmental factors. Content analysis was used to examine reports on forced migration in three Nigerian newspapers, namely, Daily Sun, The Guardian and The Nation, using the agenda setting theory. Constructed week sample of articles published over an 11-month period in 2018 was utilized to arrive at the sample size. Results show that the volume of coverage on forced migration issues is low, unillustrated and negatively slanted. Conflicts constituted the main object of attention. It is recommended that Nigerian newspapers should set proper agenda by giving prominence to issues of forced migration and also cover all sides to the issue, including migrant voices and perspectives. What is new about this study is its effort to play up migrant voices and engage in interpretative journalism, in contradistinction to the usual reportage of negative happenstances.